1977
DOI: 10.1159/000240979
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity and Its Postnatal Development in Preterm Infants

Abstract: Immunoassayable plasma renin activity (PRA) was measured in 16 healthy preterm infants of different gestational ages. A total of 52 measurements have been performed between the second week of life and the date of the expected term. PRA was found markedly increased in preterm infants and a highly significative negative correlation with postmenstrual age was proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
16
1
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 13 publications
5
16
1
1
Order By: Relevance
“…This result had already been described in the literature. [24][25][26] Blood pressure levels did not correlate with PRA levels (at birth and on the 30 th day), in either group. These results concord with other authors' results, 27,28 in which no such correlation was also found.…”
Section: Discussionmentioning
confidence: 74%
“…This result had already been described in the literature. [24][25][26] Blood pressure levels did not correlate with PRA levels (at birth and on the 30 th day), in either group. These results concord with other authors' results, 27,28 in which no such correlation was also found.…”
Section: Discussionmentioning
confidence: 74%
“…In a preliminary study on postnatal development of PRA in four preterm infants by Richer et al (22), PRA was found to be very high in the 2-3 weeks and it decreased thereafter. Neither PRA in the first 2 weeks, nor electrolyte balance and aldosterone status were determined in the study (22).…”
Section: Discussionmentioning
confidence: 90%
“…Neither PRA in the first 2 weeks, nor electrolyte balance and aldosterone status were determined in the study (22).…”
Section: Discussionmentioning
confidence: 99%
“…After the clinical development of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, the interest in the renin-angiotensin system weaned. This probably explains why our extensive literature search only identified 7 studies that reported on PRA in preterm 9,10,12 or full-term 7,8,10,11 born children. PRA peaks in the healthy newborns and falls with aging reaching mean values similar to those in adults around 8 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] For the timely prevention of kidney disease, diagnosing hypertension and renal dysfunction early in life are of primordial importance. To the best of our knowledge, only 6 former studies in preterm or full-term born children reported on plasma renin activity (PRA) [7][8][9][10][11][12] or addressed the potential role of renin in the pathogenesis of hypertension. 10,12 To bridge knowledge gaps, we undertook the PREMATCH case-control study (Prematurity as Predictor of Children's Cardiovascular and Renal Health).…”
mentioning
confidence: 99%